Quality improvement using Taguchi method in a PCB fabrication company [microfilm] - Ong, Tze Hooi (Skudai : Universiti Teknologi Malaysia, 2003)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Industri)) - Universiti Teknologi Malaysia, 2003